Maturation, morphological, motor and technical characteristics of under 16 female track and field athletes - Verbena de Freitas, J.; Zacaron Werneck, F.; Siqueira de Souza, R.; Cardoso de Castro, P. H.; Figueiredo, A. J.; Perrout de Lima, J. R. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2020)
There is growing interest in identifying morphological, motor, maturation characteristics, as well as their changes, of children and adolescents in systematized training in various sports. Knowledge of these characteristics is important for coaches and researchers because they provide parameters for assessing youth development during training. For track and field, studies on the category under 16 are scarce. Thus, the objectives of this study are to describe the profile and to design a percentile table of morphological, motor, maturation and eventspecific variables of under 16 athletes. 105 young athletes were evaluated on two consecutive days. On the first day, an anamnesis of athletes and coaches was performed. Anthropometric and anaerobic measurements were analyzed in shot put, long jump, 800 m run. On the second day, flexibility, vertical impulse, upper limb strength, speed and maximal aerobic speed were evaluated. The biological maturation was evaluated by the percentage of the predicted adulte height. A table with percentiles was prepared with the data of all athletes. Another table with the results of the whole group plus mean and standard deviation was prepared. A last table was prepared containing data divided by group of sports events. The morphological variables presented differences between the groups as to body mass, BMI and sum of skinfolds. Significant differences were observed only for the motor variable MAS. No significant differences were observed only for long jump. When divided by groups, it was evident that throwers are different from the other athletes in some morphologic variables and in specific sports events.